The development of the competency of “cultural awareness and expressions” using movie-induced tourism as a didactic resource - Pérez-García, Álvaro; Sacaluga Rodríguez, Ignacio; Moreno Melgarejo, Alberto (MDPI AG, 2022)
Competence in “Cultural awareness and expressions” requires very stimulating activities for its development, and cinema can be used as an interesting enhancer of educational action. The educational potential of the so-called movie-induced tourism, which has increased in recent years thanks to the impact of major productions such as The Lord of the Rings, Star Wars or Game of Thrones, could bring extra motivation when developing any competency including the aforementioned one. This article aims to suggest some keys on film tourism as a didactic resource and how destinations might capitalize on it through entrepreneurship. In doing so, educational establishments located within film destinations can carry out projects in this sense to work on the competence of “Cultural awareness and expressions”. Thus, an example of didactic programming will be offered based on the creation of new tourist businesses to take advantage of Lord of the Rings saga filming in San Juan de Gaztelugatxe (Vizcaya, Basque Country, Spain).
Keywords: competence development; didactic resource; educational activities; media education; movie-induced tourism; Scopus; Emerging